Contribuição para o estudo do desenho urbano de Sobral: século XIX - Rocha, Herbert de Vasconcelos (2017)
The Vila of Sobral, in the Captaincy of Ceará, was founded in 1773 at the intersection of cattle tracks, on the left bank of the middle course of the Acaraú river where, in the first half of the 18th century, the seat of the Curate of Our Lady of Conception of the Caiçara was established. Sobral was elevated to the category of City in 1841, being constituted in a great commercial warehouse of the northwest region of Ceará. This work investigates the process of urbanization of Sobral during the Empire in Brazil, when the expansion of the city presented a trajectory with reticulated tendency merging with the irregularity of the original nucleus of the eighteenth century. We investigate the role of the main modeling agents of space from primary and secondary sources, focused on the analysis of the urban problems of the studied period, seeking to plot them with a view to understanding the urban design revealed in the Sobral Railroad Plant elaborated around 1880 and in the Plan of the City of Sobral produced in 1882 for the installation of the telegraph. Our main database, in search of Sobral's nineteenth century problem, are the Minutes of the Municipal Council Sessions between 1836 and 1879 and the mailing between Sobral's Municipal Council and the Government of the Province of Ceará from 1830 to 1889. Throughout the nineteenth century issues related to salubrity, fluidity, alignment and beauty of the streets and the absence of an urban patrimony were among the guidelines of the Municipal Council discussions. We compare the primary sources with the descriptions of the City in the contemporary literature set in the city: Travel Notes by the journalist Antônio Bezerra de Menezes, who described Sobral at the end of 1884 and the realist novel Luzia-Homem by Domingos Olímpio, set in the city during the drought of 1878 – 1879 and searching for the better approximation of the sobralish built space in the second half of the nineteenth century.